1997
DOI: 10.1289/ehp.97105s3637
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic activity of natural and synthetic estrogens in human breast cancer cells in culture.

Abstract: We investigated the estrogenic activity of various environmental pollutants (xenobiotics), in particular the xenoestrogen o,p-DDT, and compared their effects with those of endogenous estrogens, phytoestrogens, and mycoestrogens on estrogen receptor binding capacity, induction of estrogen end products, and activation of cell proliferation in estrogen-sensitive human breast cancer cells in monolayer culture. We also quantified the levels of phytoestrogens in extracts of some common foods, herbs, and spices and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…It has been shown that ERK induces the AP-1 activation (Karin, 1995), thus kaempferol may promote the ALP activity in UMR-106 cells through similar mechanism. In the presence of ER, kaempferol activated AP-1 more potently than quercetin, which well resembles other finding that kaempferol antagonizes estradiol more potently than quercetin (Zava et al, 1997;Harris et al, 2005). Interestingly, isorhamnetin exhibited inhibitory effect on AP-1 activation in the presence of ER subtypes, suggesting its action may be different with quercetin or kaempferol.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been shown that ERK induces the AP-1 activation (Karin, 1995), thus kaempferol may promote the ALP activity in UMR-106 cells through similar mechanism. In the presence of ER, kaempferol activated AP-1 more potently than quercetin, which well resembles other finding that kaempferol antagonizes estradiol more potently than quercetin (Zava et al, 1997;Harris et al, 2005). Interestingly, isorhamnetin exhibited inhibitory effect on AP-1 activation in the presence of ER subtypes, suggesting its action may be different with quercetin or kaempferol.…”
Section: Discussionsupporting
confidence: 85%
“…Quercetin and kaempferol activated AP-1 reporter by both ER␣ and ER␤, which makes them behave more like ER antagonists. This further demonstrated previous observation that kaempferol and quercetin antagonized 17␤-estradiol, and kaempferol was more potent than quercetin (Zava et al, 1997;Harris et al, 2005). Contrary to quercetin and kaempferol, isorhamnetin (10-50 M) inhibited AP-1 reporter expression in the presence of ER␣ or ER␤.…”
Section: Selective Estrogen Receptor Antagonist Activitysupporting
confidence: 89%
“…This result is consistent with the results of the pooled analysis of prospective studies where the OR for women in the top quintile of oestradiol was 2.00 (95% CI ¼ 1.47 -2.71) and for women in the top quintiles of oestradiol and oestrone were 2.19 (95% CI ¼ 1.48 -3.22), respectively (TEHBCCG, 2002). As oestradiol has greater potency and binds with oestrogen receptor-a with greater affinity than oestrone (Zava et al, 1997), a stronger association of risk with oestradiol than with oestrone is usually expected. Measurement error is not likely to be responsible for our Controlling for matching factors only.…”
Section: Discussionmentioning
confidence: 99%
“…Among the agents tested, genistein showed more prominent suppression of the expression of VEGF mRNA and bFGF mRNA. Genistein, an isoflavone in soybeans, was originally recognised as a weak oestrogen and also an oestrogen antagonist at higher concentrations (Zava and Deuw, 1994). Genistein inhibits the tumour growth in various cancers in vitro and in vivo (Fotsis et al, 1995).…”
Section: Discussionmentioning
confidence: 99%